What do you (think you) need?: Perceived vs. experienced effects of need fulfillment on well-being - Neubauer, Andreas B.; Lerche, Veronika; Köhler, Friederike; Voß, Andreas (Journal of research in personality, 2020)
We compared two approaches towards assessing inter-individual differences in the effect of satisfaction and frustration of basic needs (autonomy, competence, relatedness) on well-being: perceived need effects (beliefs about the effect of need fulfillment on one’s well-being) and experienced need effects (the within-person coupling of need fulfillment and well-being). In two studies (total N = 1281), participants reported perceived need effects in a multidimensional way. In Study 2, daily need fulfillment and affective well-being were additionally assessed (daily-diary study; ten days). Associations between perceived and experienced need effects were significant (albeit small) for all three frustration dimensions, but only for one satisfaction dimension (relatedness), suggesting that they capture different constructs and might be related to different outcomes.
Gesehen am 22.03.2021